Red Ginger (Zingiber officinale var. rubrum) Massage Reduces Stiffness and Functional Disability in Elderly with Osteoarthritis - Putu Indraswari Aryanti; Joni Haryanto; Elida Ulfiana (Universitas Airlangga, 2018)
Introduction: Recent research has provided data on the efficacy of the massage therapy and the role of essential oil in the management of osteoarthritis (OA) symptoms. Although both areas of research have demonstrated strong evidence that the muscles and massage with essential oil may affect OA symptoms, massage with essential oil applied on the quadriceps muscle has received no attention. The purpose of this study was to identify the effect of red ginger massage on joint stiffness and functional disability in elderly with osteoarthritis.Methods: This study was a randomized control group pre-test and post-test experimental study design involving 62 elderly with osteoarthritis divided into two groups namely red ginger massage and control groups by random cluster sampling. The instrument used was Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Statistical test used were paired t-test and MANCOVA.Results: Baseline value of stiffness and functional disability in intervention group were 4.47 ± 1.717 and 35.93 ± 12.806. After 8 weeks stiffness and functional disability became 2.40 ± 1.380 and 19.50 ± 9.420 Stiffness and functional disability were decreased on intervention group with p-value 0.000 and 0.004. It means there was influenced by red ginger massage on stiffness and functional disability in elderly with osteoarthritis.Conclusion: Red ginger massage can be applied as a complementary treatment to help reduced joint stiffness and functional disability in addition to standard drug treatment usage in osteoarthritis disease.